Estudos espectroscópicos e de dopagem de nanocristais semicondutores de ZnS com íons Co2+ Cu2+ - Xavier, Paulo Adriano (2013)
This work reports the study of semiconductor nanocrystals, also known as quantum dots, focusing specifically on zinc sulfide (ZnS). Two different capping agents were used (glutathione and N-acetyl-L-cysteine) for the preparation of ZnS nanocrystals via aqueous route. The study aimed specifically at evaluating the efficacy of the capping agents in the stabilization of semiconductor nanocrystal suspensions towards coalescence as well as in controlling nanocrystal size and optical properties. In addition the effect of doping the ZnS nanocrystals with transition metal ions (Cu2+ and Co2+) on the photoluminescence properties has also been studied. Finally the possibility of energy transfer between the semiconductor nanocrystals and the safranine dye was also evaluated. Spherical-shaped glutathione and N-acetyl-L-cysteine-capped ZnS nanocrystal were obtained with diameters below 5 nm free from coalescence, showing that both iv capping agents were efficient as stabilizers. Both capping agents lead to the formation of ZnS nancrystals with blue fluorescence, typical of the involvement of surface defect states of ZnS. However, samples prepared with glutathione exhibited higher fluorescence intensities than those obtained with N-acetyl-L-cysteine. Upon doping glutathione-capped ZnS nanocrystals with both copper and cobalt the fluorescence intensities decreased gradually following the increase in nominal concentration of dopants, suggesting that cobalt ions played a similar role as copper. Considering both the effect on the intensities and the absence of d-d metal transitions this study suggests that doping reduced the concentration of cation vacancies as well as the involvement of at least one cobalt state in the transition processes. Changes in emission wavelength with different dopant concentrations were not observed probably owing to lack of influence on the nanocrystal size. Finally the preliminary study of fluorescence quenching of semiconductor nanocrystals by safranine dye indicated that significantly low concentrations were able to quench the emissions. Different components of the emission band were distinctly affected. Data analysis by Stern-Volmer plots suggested the occurrence of more than one transfer processes (energy and/or electron transfer). This study will be refined in future works.